Verbal aspect in the Book of Revelatio n the function of Greek verb tenses in John's Apocalypse - Mathewson, David. (Linguistic Biblical Studies, 2010)
The book of Revelation is well-known for its grammatical infelicities. More specifically, Revelation exhibits apparently \'odd\' use of Greek verb tenses. Most attemtps to describe this \'odd\' use of verb tenses start with the assumption that Greek verb tenses are primarily temporal in meaning. In order to explain Revelation's apparent violation of these temporal values, scholars have proposed some level of semitic influence from the Hebrew tense system as making sense of this \'odd\' use of tenses. However, recent research into verbal aspect, which calls into question this temporal orientation, and suggests that Greek verb tenses grammaticalize aspect and not time, has opened up new avenues for explaining the Greek verb tense usage in Revelation. This book applies verbal aspect theory to tense usage in Revelation and focuses on how the tenses, as communicating verbal aspect, function within sections of Revelation.